Evaluation of antimicrobial efficacy of sodium hypochlorite, propolis, octenidine dihydrochloride and chlorhexidine on microorganisms - Abdullah Kılıç; Alper Kustarci; Demet Altunbaş; Elif Oktay; Ülkü Özan (Cumhuriyet University, 2011)
Objectives: The aim of this present study was to evaluate the antimicrobial effect of  2.5% sodium hypochlorite (NaOCl), 12.5% propolis, 25% propolis, octenidine dihydrochloride (OCT) and 2% chlorhexidine (CHX) on microorganisms with different structural characteristics. Materials and Methods: S. aureus, E. faecalis, E. coli and C. albicans were included in the study. Pre-sterilized paper discs (6 mm in diameter) were soaked with the test solutions and placed on the plates, following Muller-Hinton agar plates were inoculated with the microbial suspensions. Then zones of inhibition were recorded and the results were analysed statistically. 2.5% NaOCl, 2% CHX and OCT produced inhibitory zones against all microorganisms tested. Statistical analysis was carried out with analyses of variance (ANOVA). Differences were identified by post-hoc Bonferroni test. The level of significance was set at p=0.05. Results: NaCl was ineffective against all microorganisms; however, 2.5% NaOCl, 2% CHX and OCT produced inhibitory zones against all microorganisms tested. 2.5% NaOCl and 2% CHX showed significantly larger average zones of inhibition compared to the other experimental irrigants (p<0.05). While 12.5% propolis extract produced only slight inhibition on S. aureus, 25% propolis extract was effective on S. aureus, E. faecalis and C. albicans. Conclusions: The present study showed that 2.5% NaOCl and 2% chlorhexidine had superior antimicrobial effects than other irrigants used.